Development of a rapid cell‐fusion‐based phenotypic HIV‐1 tropism assay - Teeranaipong, Phairote; Hosoya, Noriaki; Kawana‐Tachikawa, Ai; Fujii, Takeshi; Koibuchi, Tomohiko; Nakamura, Hitomi; Koga, Michiko; Kondo, Naoyuki; Gao, George F; Hoshino, Hiroo; Matsuda, Zene; Iwamoto, Aikichi (Journal of the International AIDS Society, 2013)
Introduction A dual split reporter protein system (DSP), recombining Renilla luciferase (RL) and green fluorescent protein (GFP) split into two different constructs (DSP1–7 and DSP8–11), was adapted to create a novel rapid phenotypic tropism assay (PTA) for HIV‐1 infection (DSP‐Pheno). Methods DSP1–7 was stably expressed in the glioma‐derived NP‐2 cell lines, which expressed CD4/CXCR4 (N4X4) or CD4/CCR5 (N4R5), respectively. An expression vector with DSP8–11 (pRE11) was constructed. The HIV‐1 envelope genes were subcloned in pRE11 (pRE11‐env) and transfected into 293FT cells. Transfected 293FT cells were incubated with the indicator cell lines independently. In developing the assay, we selected the DSP1–7‐positive clones that showed the highest GFP activity after complementation with DSP8–11. These cell lines, designated N4R5‐DSP1–7, N4X4‐DSP1–7 were used for subsequent assays. Results The env gene from the reference strains (BaL for R5 virus, NL4‐3 for X4 virus, SF2 for dual tropic virus) subcloned in pRE11 and tested, was concordant with the expected co‐receptor usage. Assay results were available in two ways (RL or GFP). The assay sensitivity by RL activity was comparable with those of the published phenotypic assays using pseudovirus. The shortest turnaround time was 5 days after obtaining the patient's plasma. All clinical samples gave positive RL signals on R5 indicator cells in the fusion assay. Median RLU value of the low CD4 group was significantly higher on X4 indicator cells and suggested the presence of more dual or X4 tropic viruses in this group of patients. Comparison of representative samples with Geno2Pheno [co‐receptor] assay was concordant. Conclusions A new cell‐fusion‐based, high‐throughput PTA for HIV‐1, which would be suitable for in‐house studies, was developed. Equipped with two‐way reporter system, RL and GFP, DSP‐Pheno is a sensitive test with short turnaround time. Although maintenance of cell lines and laboratory equipment is necessary, it provides a safe assay system without infectious viruses. With further validation against other conventional analyses, DSP‐Pheno may prove to be a useful laboratory tool. The assay may be useful especially for the research on non‐B subtype HIV‐1 whose co‐receptor usage has not been studied much.